Pemanfaatan Digital Marketing Untuk Peningkatan Potensi Pariwisata Desa Kaduela Kuningan-Jawa Barat - Maudiarti, Santi; Achmadi, Mochammad; Pramanik, Purwanti Dyah (Jurnal Pemberdayaan Pariwisata; Vol 6 No 1 (2024): Jurnal Pemberdayaan Pariwisata, 2024)
This activity aims to provide skills in creating digital marketing and knowledge regarding tips for creating sentences for content in digital marketing to attract more tourists to visit Kaduela village. The targets for assistance in creating digital marketing include homestay owners, tourism actors who want to create tour packages, village youth who want to be skilled at creating exciting content, and village officials who market the tourism potential of Kaduela Kuningan village, West Java. The implementation method involves analyzing community needs, program planning, preparing training materials, interactive training with a practical approach, field practice, and mentoring and evaluation carried out by instructors during and after this activity. Participants are given an in-depth understanding of digital marketing, including websites, social media, email marketing, and SEO, which is vital for tourism businesses. They also receive practical training in creating attractive websites, optimizing social media content, and using Google Ads. Discussions between participants and activity resource persons build supportive communities in villages, which is essential for the growth and adaptation of the tourism industry. This activity strengthens the capacity and competitiveness of tourism actors in Kaduela Village through education, training, and collaboration . Keywords: digital marketing, tourism potential